PROFIL KESULITAN BERTANYA PADA PROSES PEMBELAJARAN PERKEMBANGAN HEWAN MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS ISLAM RIAU PEKANBARU: (The Profiles of Questioning Difficulty during Animal Development Study Process for Biology Education Student) - Suryanti Suryanti; Sudarmi Sudarmi; Salsabyla Fadheela (Perspektif Pendidikan dan Keguruan, 2019)
This study aims to determined factors of questioning difficulty during learning process on Animal Development study. The type of study was survey, using questionnaire, interview, and documentation as study’s instrument. The population subject of this study was third semester student of Biology Education with total 70 students. Analysis method was using descriptive method. As the result of the study shown that questioning difficulty was affected by internal factor 56,21% categorized as adequately and affected by external factor by 61,14% categorized as high. The percentage of students who created question was 42,86% categorized, as adequately, students who were not raise question 57.14% categorized as adequately. During study process, student who able to make questions was at the level of: level C1 (9.64%), level C2 (67,47%), level C3 (14,46%) and level C4 (1,20%) Keywords: Questioning Difficulty Profiles, Internal and External Factors, Student who raised questions, Student who did not raise question, Question Level C1, C2, C3, and C4, Animal Development Study